Raman Studies of Two-Dimensional Group-VI Transition Metal Dichalcogenides under Extreme Conditions - Yang Yang; Yongping Han; Renfei Li (Crystals, 2023)
In the past decade, two-dimensional (2D) transition metal dichalcogenides (TMDs) have attracted increasing attention because of their striking physical properties and extensive applicability. Meanwhile, Raman spectroscopy has been demonstrated to be a feasible tool and is extensively employed in research on 2D TMDs. In recent years, the deployment of Raman spectroscopy under extreme conditions has elucidated the physical properties of TMDs. In this review, we focus on the extreme-condition Raman spectroscopy of typical group-VI TMDs, which are classified and discussed under the three extreme conditions of low temperature, high pressure and high magnetic field. The conclusion presents the most pressing challenges and attractive future opportunities in this rapidly developing research field.